A history of the Federal Reserve. - Meltzer, Allan H. (University of Chicago Press, 2003)
This first volume of Allan H. Meltzer's history of the Federal Reserve System covers the period from the Federal Reserve's founding in 1913 through the Treasury-Federal Reserve Accord of 1951. To understand why the Federal Reserve acted as it did at key points in its history, Meltzer draws on meeting minutes, correspondence, and other internal documents (many made public only during the 1970s) to trace the reasoning behind its policy decisions. He explains why the Federal Reserve remained passive throughout most of the economic decline that led to the Great Depression, and how the Board's actions helped to produce the deep recession of 1937 and 1938. He also highlights the impact that individuals had on the institution, such as Benjamin Strong, governor of the Federal Reserve Bank of New York in the 1920s, who played a large role in the adoption of a more active monetary policy by the Federal Reserve. From attempts to build a new international financial system at the London Monetary and Economic Conference of 1933 to the Bretton Woods Agreement of 1944 that established the International Monetary Fund and the World Bank, Meltzer also examines the influence the Federal Reserve has had on international affairs.